Domains of Digital Marketing Channels in the Sharing Economy. Issue 1 (3rd April 2017) - Key, Thomas Martin
Abstract : The sharing economy has experienced major growth in a short period with little academic research that has looked into possible logistic factors that may have contributed to this phenomenon. This article explores the domains of digital marketing channels—specifically e-mail marketing, social media marketing, and search engine marketing—to understand how they can contribute to growth for organizations in the sharing economy. A detailed conceptual model of the decision spectrum necessary to coordinate digital marketing channels is presented and a special case is made for the role branded-mobile applications play in this context. In particular, branded-mobile applications leverage three embedded components to overcome common deterrents for participating in the sharing economy: trust, utility, and user experience.